2019
DOI: 10.1186/s12913-019-4588-x
|View full text |Cite
|
Sign up to set email alerts
|

THRIVE study protocol: a randomized controlled trial evaluating a web-based app and tailored messages to improve adherence to adjuvant endocrine therapy among women with breast cancer

Abstract: BackgroundLong-term use of adjuvant endocrine therapy (AET) among women with early-stage, hormone receptor-positive breast cancer significantly reduces the risk of hospitalizations, cancer recurrence, and mortality. AET is associated with adverse symptoms that often result in poor adherence. A web-enabled app offers a novel way to communicate and manage symptoms for women on AET. In a region with significant racial disparities in breast cancer outcomes, our study tests the impact of a web-enabled app that coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…44 In a study of 22 breast cancer survivors, semi-structured in-depth interviews identified that social support provides some women with educational, physical, and emotional benefits that may influence their continuation of AET. 45 On-going clinical trials are investigating alternative interventions using telephone-based coping skills training 46 and web-based applications that collects patient-reported symptoms to their healthcare teams 47 . Thus, drawing parallels to endocrine therapy adherence for carcinoma, our study reiterates the currently unmet clinical need for interventions geared specifically towards minimizing racial and ethnic gaps in the use of chemoprevention among high-risk populations of different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 In a study of 22 breast cancer survivors, semi-structured in-depth interviews identified that social support provides some women with educational, physical, and emotional benefits that may influence their continuation of AET. 45 On-going clinical trials are investigating alternative interventions using telephone-based coping skills training 46 and web-based applications that collects patient-reported symptoms to their healthcare teams 47 . Thus, drawing parallels to endocrine therapy adherence for carcinoma, our study reiterates the currently unmet clinical need for interventions geared specifically towards minimizing racial and ethnic gaps in the use of chemoprevention among high-risk populations of different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Although the median age at diagnosis was comparable between non-Hispanic white and non-Hispanic black women, Hispanic women tended to be younger at the time of an atypia diagnosis (median age in years [IQR]; Hispanic: 46 [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]; non-Hispanic black: 57 [49-65]; non-Hispanic white: 54 [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]; p=0.05; Table 1). Accordingly, pre-menopausal status was over-represented among Hispanic women (Hispanic: 40%; non-Hispanic black: 15%; non-Hispanic white: 16.9%; p=0.02).…”
Section: Breast Cancer Risk Factors By Remmentioning
confidence: 99%
“…The study will randomize 300 patients into three separate arms: 1. a group that receives weekly reminders through the application, 2. a group that receives weekly reminders and tailored feedback, and a usual care group. The primary endpoint is medication adherence as determined using an electronic pillbox [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…We conducted a literature review on interventions that improve endocrine therapy adherence, which identified 2 consequential gaps in existing intervention research: use of education only interventions and a lack of cultural adaptations [9][10][11][12][13][14][15][16]. Next, we examined commercially available cancer and medication adherence mobile health (mHealth) apps as a possible option to address these gaps and assist African-American women with endocrine therapy adherence [17][18][19][20][21]. Unfortunately, available cancer and medication adherence apps also have several areas that cause concern: (1) a lack of adequate development or testing in clinical practice [17,22,23], (2) a lack of input from patients or providers resulting in significant usability problems [24][25][26], and (3) a lack of scientifically valid information, with the majority of cancer-related apps created to promote a pharmacy or organization and not to assist African-American women with endocrine therapy adherence [20,26].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, over 90% of medication adherence mHealth apps were simple reminders and not effective in improving adherence [20]. Cancer mHealth apps research has explored functionality and acceptability, but only one evaluated effectiveness or clinical outcomes [17][18][19].…”
Section: Introductionmentioning
confidence: 99%